Differential protein expression and localization of CYP450 enzymes in three species of earthworm; is this a reflection of environmental adaptation?. (March 2017) - Lu, Xiaoxu; Li, Yinsheng; Thunders, Michelle; Cavanagh, Jo; Matthew, Cory; Wang, Xiuhong; Zhou, Xinchu; Qiu, Jiangping
Abstract: Cytochrome P450 (CYP450) is a hemoprotein superfamily, among which CYP1, CYP2 and CYP3 play a major role in the metabolism of vast array of xenobiotics and endobiotics. This paper reports on three CYP enzyme variants (CYP1A2, CYP2E1 and CYP3A4) in three species of earthworm ( Eisenia fetida, Metaphire guillelmi and Amynthas carnosus) . The relative expression levels and localization of the three associated proteins were investigated at three life-cycle points (juvenile, sub-adult and adult), through comparison of anterior and posterior body tissue and between specific organs (body wall, intestine and reproductive tissues) using western blot analysis. This study confirmed the presence of CYP3A4, CYP1A2 and CYP2E1 in all three species of earthworm tested. The levels of expression varied with earthworm species, age, and body location. These differences in occurrence of the three CYP enzymes appeared to reflect the ecological niche (the spatial and temporal location and functional relationship of each individual or population in populations or communities), and the likelihood of contact with soil contaminants of the respective species. These results may help to explain why earthworms are capable of adapting to very different and extensively polluted soil environments and provide important data for subsequent ecotoxicology and ecological adaptability studies. Highlights: CYP1A2, CYP2E1 and CYP3A4 proteins were detected in 3 species of earthworm. CYP450 protein levels varied by species and usually increased with age. CYP protein levels is higher in anterior parts of 2 species and posterior parts in a third. CYP450 proteins were often concentrated in the body wall and intestine. We propose CYP450 protein expression reflects the ecological niche of earthworm species.